2011
DOI: 10.1002/ajpa.21490
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lactase persistence polymorphism in ancient and present‐day Hungarian populations

Abstract: The prevalence of adult-type hypolactasia varies ethnically and geographically among populations. A C/T-13910 single nucleotide polymorphism (SNP) upstream of the lactase gene is known to be associated with lactase non-persistence in Europeans. The aim of this study was to determine the prevalence of lactase persistent and non-persistent genotypes in current Hungarian-speaking populations and in ancient bone samples of classical conquerors and commoners from the 10th-11th centuries from the Carpathian basin; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 57 publications
3
15
1
2
Order By: Relevance
“…Although lactase persistence reaches up to 60-90% in Central-European and Northern European populations, it is much less frequently present in Southern European, Middle-Eastern, African and some South-Asian populations, while being completely absent in the rest of the world population. [1][2][3] The persistent activity of the lactase enzyme (ie, lactase phlorizin hydrolase, encoded by the lactase gene LCT) during adulthood, expressed especially in the intestine, has been demonstrated to be linked with variations in the lactase promoter, such as a C/T transition in the promoter region 13910 basepairs upstream of the LCT gene (rs4988235), which is suggested to influence LCT gene expression. 4 The T allele, dominant over the C allele, has been described to be the allele associated with lactase persistence in European populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although lactase persistence reaches up to 60-90% in Central-European and Northern European populations, it is much less frequently present in Southern European, Middle-Eastern, African and some South-Asian populations, while being completely absent in the rest of the world population. [1][2][3] The persistent activity of the lactase enzyme (ie, lactase phlorizin hydrolase, encoded by the lactase gene LCT) during adulthood, expressed especially in the intestine, has been demonstrated to be linked with variations in the lactase promoter, such as a C/T transition in the promoter region 13910 basepairs upstream of the LCT gene (rs4988235), which is suggested to influence LCT gene expression. 4 The T allele, dominant over the C allele, has been described to be the allele associated with lactase persistence in European populations.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis has been described in literature as the 'culture-historical hypothesis' 7,8 and has been supported by recent studies in the Neolithic samples from Central, Mediterranean and Northern Europe [9][10][11] and medieval samples from Central Europe. 3 Burger et al 9 reported the absence of lactase persistence in a total number of nine early Neolithic Central Europeans (7500 YBP), which argues that in this era Europeans were predominantly lactase deficient in adulthood. The absence of lactase persistence is also reported by Lacan et al 11 in 26 samples from a late Neolithic burial located in Southern France.…”
Section: Introductionmentioning
confidence: 99%
“…Csontokban a C/C allél 87%, a C/T 4%, a T/T 9%-ban volt jelen -ez ázsiai szárma-zásra utal, a 181 jelenkori egyénben az arányok 39%, 50% és 11%: ez utóbbiak megegyeznek a környező országok lakosságában észleltekkel, ami viszont a keveredésre utal. Ugyanaz a szerzőcsoport C/C-13910 genotípus gyakoriságát 37%-nak találta: az egyének többsé-gében a H 2 -teszt pozitív volt [21,22].…”
Section: Epidemiológiaunclassified
“…Bersaglieri et al (3) showed clear evidence of recent positive selection on this haplotype in Europeans, presumably because of the selective advantage conferred by being able to digest milk and milk products. Nagy et al (57) tested for the lactase-persistence haplotype in 23 Hungarian individuals from 1,000–1,100 ybp and found it at a frequency of only 11%, even though that haplotype has a frequency of 77% in present-day Hungarians. Nagy et al concluded that the low frequency of the lactase-persistence haplotype in aDNA confirms the recent Asian origin of early Hungarians.…”
Section: Temporal Series Of Allele Frequenciesmentioning
confidence: 99%